The Error of NO Response and its Influence on the Validity and Reliability of Household Opinion Surveys - Quiroz Vera, Eduardo Fernando (2006)
This research exposes the urgent need to become aware of the magnitude and importance of non-sampling errors in household opinion polls, especially the NON-RESPONSE ERROR, which threatens to invalidate or bias the results of any research in one direction.